2018
DOI: 10.1136/medethics-2017-104203
|View full text |Cite
|
Sign up to set email alerts
|

Making medical decisions for an incompetent older adult when both a proxy and an advance directive are available: which is more likely to reflect the older adult’s preferences?

Abstract: ISRCTN89993391; Post-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…93.4% of were reported by their caregivers to have an advance directive and 96.1% of decedents with advance directives were reported to have assigned a health care agent. Our high rates of advance directive possession and health care agent designation are concordant with recent studies in community-dwelling populations of people with dementia in the United States [27,37,38] . To our knowledge, there have been two previous studies assessing goals of care conversations between people with dementia and their caregivers [27,28] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…93.4% of were reported by their caregivers to have an advance directive and 96.1% of decedents with advance directives were reported to have assigned a health care agent. Our high rates of advance directive possession and health care agent designation are concordant with recent studies in community-dwelling populations of people with dementia in the United States [27,37,38] . To our knowledge, there have been two previous studies assessing goals of care conversations between people with dementia and their caregivers [27,28] .…”
Section: Discussionsupporting
confidence: 86%
“…Those with dementia may discuss wishes with lawyers in the course of drafting directives, but such conversations and documents are not always revealed to caregivers, sometimes due to attorneyclient confidentiality [33] . As a result, surrogate decision-makers often poorly predict the preferences of people with dementia [34][35][36] and lack concordance with advance directives [37,38] .…”
Section: Introductionmentioning
confidence: 99%
“…5 Further, other studies have found preliminary evidence that patients' preferences documented in LWs better reflect their wishes and preferences than the predictions made by their designated surrogates. 6 This is additionally supported by research in recent years that has found that the majority of patients (especially those with advance directives) do have stable end-of-life preferences over time. 2,7 Thus, when these findings are combined with the additional concerns regarding the accuracy of surrogate decision-making, there does not seem to be justification for prioritizing patients' HcPOAs over their LWs based upon this concern regarding the reliability of the documented preferences in LWs.…”
mentioning
confidence: 81%
“…Three (8.8%) articles tested interventions aimed at improving dementia care dyad ACP concordance ( Matheis-Kraft & Roberto, 1997 ; Towsley et al 2022 ; Volandes et al 2009 ). Two (5.8%) articles tested whether surrogate decision makers were more accurate than a written advance directive ( Bravo et al, 2018 ) or an actuarial model ( Smucker et al, 2000 ). One (2.9%) intervention tested whether older adults with dementia could effectively communicate their end-of-life wishes ( Song et al, 2019 ).…”
Section: Part 1: Scoping Reviewmentioning
confidence: 99%